1995
DOI: 10.1111/j.1365-2249.1995.tb05563.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of a unique peptide epitope of the mycobacterial and human heat shock protein 65–60 antigen by T cells of patients with recurrent oral ulcers

Abstract: SUMMARYT cell epitopes of the 65-kD heat shock protein (hsp) were investigated in patients with recurrent oral ulcers (ROU). Peripheral blood mononuclear cells were stimulated with overlapping synthetic peptide (1 5ers), derived from the sequence of the 65-kD hsp of Mycobacterium tuberculosis. Specific lymphoproliferative responses were stimulated only with peptide 91-105 in ROU, compared with healthy or disease controls (P<0-01). This was confirmed by studying 760 short term cell lines generated with the 65-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 16 publications
0
20
0
3
Order By: Relevance
“…Oral streptococci have also been implicated (Hasan et al 1995). So far, however, no bacterial species have been conclusively shown to be the causative agents of RAS.…”
Section: Introductionmentioning
confidence: 99%
“…Oral streptococci have also been implicated (Hasan et al 1995). So far, however, no bacterial species have been conclusively shown to be the causative agents of RAS.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that RAS can have many pre‐disposing factors including stress, nutritional deficiencies, trauma, hormonal changes, and diet. Other contributors may be psychological factors, and there are occasional associations with Coeliac disease and other immunological disorders (4, 5) found that RAS appears to have an immuno‐genetic background, with an association with a positive family history in some cases, weak histocompatibility locus antigen (HLA) associations (6), and the implication of heat shock proteins (7). There may also be associations with immunologically related diseases, such as immunodeficiencies, various allergies and atopic disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…Hasan et al (1995) showed that T lymphocytes of patients with RAS recognized a unique peptide sequence of the mycobacterial and human hsp 65 to 60 antigen. Responses to a human 60 kDa hsp peptide were also raised.…”
Section: Single Persistent Ulcermentioning
confidence: 99%